HISTORIOGRAPHY OF THE ESTABLISHMENT OF NEW HIGHER EDUCATIONAL INSTITUTIONS IN UZBEKISTAN (PART 1) (World Bulletin of Social Sciences, 2023)
In the world experience, the field of education is always one of the main criteria that determines the level of development of the country, the well-being of the people, and cultural achievements. In particular, it is possible to determine the level of spiritual development of the people by studying the history of science and the education system. Especially until now, the information about the achievements and shortcomings of the historiography of the higher education system of Uzbekistan in the 20s and 30s of the 20th century is explained by the extremely comprehensive information. This article describes the historiography and characteristics of the new higher educational institutions in Uzbekistan.